Simultaneous Occurrence of Partial and Complete Fetal Mummification in a Goat with Prolonged Gestation - Nishat, Tarana; Bhavna; Singhal, Sumit; Kumar, Alok; Kumari, Rakhi; Perveen, Zinnat (The Indian Journal of Animal Reproduction, 2025)
A four-year-old non-descript goat in her 5th parity was presented to Veterinary Clinical Complex, Bihar Veterinary College, Bihar Animal Science University, Patna, Bihar. Owner complained that the animal was pregnant but even after 6 months, the animal did not show any signs of parturition however, the abdomen still showed enlargement. Kidding was induced by synthetic PGF2 alpha analogue and estradiol benzoate. Among three fetuses delivered, one was completely and two were partially mummified.